1999
DOI: 10.1103/physrevb.59.r5300
|View full text |Cite
|
Sign up to set email alerts
|

Optical anisotropy in self-assembled InP quantum dots

Abstract: Strong optical anisotropy is observed in the photoluminescence ͑PL͒ bands of both the InP self-assembled quantum dots and the Ga 0.5 In 0.5 P matrix. From the linearly polarized PL spectra measured under weak excitation, we found that large size quantum dots show strong anisotropy. The luminescence from a single quantum dot observed by the micro-PL technique revealed a doublet fine structure of the exciton levels that obey the linear polarization selection rule. The observed fine structure is shown to arise fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
75
2

Year Published

2000
2000
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 16 publications
5
75
2
Order By: Relevance
“…A polarization rate of 30% is observed which is explained as due to size and shape anisotropies. Theoretically, it has been shown that circularly symmetric QDs can have a preferred optical polarization direction 7,9 due to composition gradients 7,10 and strain distribution 2,9,11 within the QDs.…”
Section: Introductionmentioning
confidence: 99%
“…A polarization rate of 30% is observed which is explained as due to size and shape anisotropies. Theoretically, it has been shown that circularly symmetric QDs can have a preferred optical polarization direction 7,9 due to composition gradients 7,10 and strain distribution 2,9,11 within the QDs.…”
Section: Introductionmentioning
confidence: 99%
“…In theory, the polarization properties of photon pairs emitted through these two decay paths result entirely from properties of the optically-active 1X doublet [10,11,12]. For a symmetric quantum dot, the two 1X states are degenerate, and the two decay paths become "indistinguishable," ideally producing polarization-entangled photons [9].…”
mentioning
confidence: 99%
“…The strong optical anisotropy is due to the formation of the natural superlattice. 9,27 The PL spectrum Wavelength (nm)…”
Section: A Photoluminescence and Pump-probe Measurementsmentioning
confidence: 99%
“…An interesting aspect of InP QDs is that the optical anisotropy is due to a combined effect of the shape as well as structural anisotropy. 9,10,[27][28][29][30] In this paper we demonstrate the use of time-resolved differential reflectivity for studying excitonic structure in InP QDs. The advantage of this technique is that it is relatively simple to implement and its time resolution is solely limited by the laser pulse width.…”
Section: Introductionmentioning
confidence: 99%